α-lipoic acid protects the ischemia reperfusion injury in human simultaneous kidney-pancreas transplantation. - Ambrosi, Nella Gabriela (2016)
Background: Multiple factors have been implicated in the process of ischemia-reperfusion injury (IRI) in organ transplantation. Among these factors, oxidative damage seems to initiate the injury. α-lipoic acid (ALA) is a potent antioxidant that is used in patients with diabetic polyneuropathy. The aim of the present study was to determine the effect of ALA in patients undergoing simultaneous kidney-pancreas transplant by evaluating the functional recovery of the graft and biochemical markers of IRI. Methods: Twenty-six patients were included in the following groups: (i) untreated control; (ii) donor and recipient (DR) ALA-treated, in which ALA was administered both to the deceased donor and to the recipients; and (iii) recipient ALA-treated group. The expression of inflammatory genes, as observed in biopsies taken at the end of surgery, as well as the serum cytokines, secretory leukocyte protease inhibitor, regenerating islet-derived protein 3β/pancreatitis-associated protein, amylase, lipase, glucose, and creatinine levels were quantified as markers of organ function. Results: The DR group showed high levels of TGFβ and low levels of C3 and TNFα in the kidneys, whereas high levels of C3 and heme oxygenase were identified in pancreas biopsies. Decreases in serum IL-8, IL-6, secretory leukocyte protease inhibitor, and regenerating islet-derived protein 3 β/pancreatitis-associated protein were observed after surgery in the DR group. Serum lipase and amylase were lower in the DR group than in the control and recipient groups. Early kidney dysfunction and clinical pancreatitis were higher in the control group than in either treatment group. Conclusions: These results show that ALA preconditioning is capable of reducing inflammatory markers while decreasing early kidney dysfunction and clinical posttransplant pancreatitis.